A Case of Allergic Bronchopulmonary Aspergillosis (ABPA) in a Patient with a History of Cocaine Use and Tuberculosis - Noura Ayoubi; Samuel Jalali; Nikesh Kapadia (Case Reports in Medicine)
Aspergillosis refers to a spectrum of disorders that can occur due to colonization with the Aspergillus fungus. Allergic bronchopulmonary aspergillosis (ABPA) is an airway hypersensitivity reaction to the fungus that is almost exclusively seen in patients with cystic fibrosis or asthma. Here, we present a case of ABPA in a patient with a history of chronic cocaine use and tuberculosis and no history of asthma or cystic fibrosis. The patient had presented with progressively worsening dyspnea for three months as well as a 20-pound weight loss. Diagnosis was made with an elevated IgE against Aspergillus and chest CT findings, which included bronchiectasis and tree-in-bud nodular opacities. The patient was treated with IV methylprednisolone followed by a 4-day course of oral prednisone, with significant improvement. It is our hope to make healthcare providers aware of the potential presence of ABPA in chronic cocaine users and patients with tuberculosis, both of which are not traditionally associated with this condition.